PENGARUH KOMITE AUDIT, KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN PUBLIK, INDEX DISCLOSURE TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan yang Termasuk dalam Indeks LQ 45 Tahun 2010-2012) - , OKTARINA RATNA PUTRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Earnings management occurs due to a conflict of interest between shareholders and management. Discretionary accruals is a proxy of earning management, it is an accrual accounting method that provides flexibility for management to choose a particular accounting method. The main purpose of this research is to examine the effect of audit committees, institutional ownership, public ownership and disclosure index to earnings management. The sampling method used is purposive sampling. The samples used were 27 companies that consistently include in LQ 45 for three years, in 2010-2012, so this study using 87 samples. This study used multiple linear regression analysis. The methods of analyzing consist of the classical assumption test, F test and t test. The results of this study indicate that the independence of the audit committee, audit committee effectiveness and public ownership have a significant effect on earnings management while institutional ownership structure and disclosure index has no effect on earnings management.